The association between intima media thickness, central obesity and diastolic blood pressure in obese and owerweight children: A cross-sectional school-based study - Elkiran, Ozlem; Yilmaz, Erdal; Koc, Mustafa; Kamanli, Ayhan; Ustundag, Bilal; Ilhan, Necip (Elsevier Ireland Ltd, 2013)
Objective: To examine relationship between carotid intima-media thickness (IMT) and central obesity, cardiovasculary risk factors, and chronic inflammation markers in overweight and obese schoolchildren in Eastern Turkey. Methods: A cross-sectional school-based survey on 2765 schoolchildren was performed. We collected the clinical data (age, sex, percentage of body fat, and measured systolic blood pressure [BP] and diastolic BP, triglycerides, high-and low-density lipoprotein cholesterol, glucose, insulin, homocysteine and high-sensitivity C-reactive protein) in 67 obese and 24 overweight children. The control group was composed of nonobese children of similar age and sex. Results: Mean systolic and diastolic BP values in the cases of overweight and obese groups were higher than those in the control group cases (p = 0.001). Obese and overweight children demonstrated a significantly thicker intima media as compared with the control group (p = 0.001). Carotid IMT was significantly correlated to the body mass index (r = 0.396, p = 0.001), fat mass percentage (r = 0.257, p = 0.036), waist circumference (r = 0.390, p = 0.001), diastolic BP (r = 0.266, p = 0.030), glucose (r = 0.250, p = 0.042), and high-sensitivity C-reactive protein levels (r = 0.269, p = 0.001) in the obese group. In multiple linear regression analysis, carotid IMT correlated significantly to waist circumference (p = 0.045), and diastolic BP (p = 0.031) in obese group. Conclusions: Obesity is related to cardiovascular risk factors leading to early atherosclerosis in schoolchildren. There is a relationship between atherosclerosis, and central obesity, diastolic BP, and chronic inflammation. Waist circumference measurement is more sensitive than other anthropometric measurements in predicting obesity and associated complications. (c) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Childhood obesity; Early atherosclerosis; Intima media thickness